Storying multipolar climes of the Himalaya, Andes and Arctic
1 online resource (307 p.).
Keywords: This book initiates multipolar climate/clime studies of the world's altitudinal and latitudinal highlands with terrestrial, experiential, and affective approaches. Framed in the environmental humanities, it is an interdisciplinary, comparative study of the mutually-embodied relations of climate, nature, culture, and place in the Himalaya, Andes, and Arctic. Innovation-driven, the book offers multipolar clime case studies through the contributors' historical findings, ethnographic documentations, and diverse conceptualizations and applications of clime, an overlooked but returning notion of place embodied with climate history, pattern, and changes. The multipolar clime case studies in the book are geared toward deeper, lively explorations and demonstrations of the translatability, interchangeability, and complementarity between the notions of clime and climate. "Multipolar" or "multipolarity" in this book connotes not only the two polar regions and the tectonically shaped highlands of the earth but also diversely debated perspectives of climate studies in the broadest sense. Contributors across the twelve chapters come from diverse fields of social and natural sciences and humanities, and geographically specialize, respectively, in the Himalayan, Andean, and Arctic regions. The first comparative study of climate change in altitudinal and latitudinal highlands, this will be an important read for students, academics, and researchers in environmental humanities, anthropology, climate science, indigenous studies, and ecology. Chapters 8 and 9of this bookare freely available as a downloadable Open Access PDF at Link under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.